Aplicación del proceso de atención de enfermería en paciente 58 años con Artrosis. - Almeida Suarez, Byron Patricio (2023)
The objective of this case study is to develop the application of the nursing care process for a patient diagnosed with osteoarthritis, whose age was 58 years. The methodology used in this research corresponds to a clinical case study. Osteoarthritis is a joint disease that mainly affects older adults and is characterized by degeneration of articular cartilage. According to the World Health Organization, osteoarthritis is the third major health problem in developed countries, being considered the most common disease of the musculoskeletal system in all ethnic groups and geographic regions, affecting 80% of the population over 50 years in 10% of the world population older than 50 years. Its importance lies not only in reducing the quality of life of the elderly, but also in the pressure it generates on the health system and should be considered a marker of multimorbidity since it is associated with diabetes (in 8.3%) and depression (in 7.8%), which explains the high costs for the health system in caring for those who suffer from this condition. The factors are divided into two groups: those that act at the systemic level and those that act at the articular level. Osteoarthritis mainly affects the knees, hands, feet, hips, shoulders and spine. It is characterized by insidious, sometimes localized, joint pain that worsens with physical activity. To achieve maximum clinical benefit, your treatment requires an integrated and individual approach based on the wishes of the patient.